Desafios do fazer na gestão da cultura - Soares, Sebastião José (2013)
This doctoral thesis focuses on two experiences of cultural management, in which I was directly involved. One of then happened from 1997 to 2004 at the Municipal Culture in Itapecerica da Serra city and the other in the context of the Tide Setubal Foundation that developed in Sao Miguel Paulista, neighborhood of East Region of São Paulo capital. Although the culture managements happen in different universes, both are characterized by the coexistence of managers with activities and representations of who belonged to and participated in these experiments approached in a comparative perspective, they show the importance of ways of management of cultural policies, in addition to administrative aspects. In implementation of projects and programs of culture, a counterpoint comes between the "do to" and "do with" the target public, men and women, young and not so young. Thus the important role assumed by the target public, since the cultural actions are based on a careful view and a receptive listening to their experiences, knowledge and practices related to everyday life that are neither always taken into account, nor are they considered as specific demands